Environmental sustainability in developing countries: Understanding the criticality of financial inclusion and globalization. (9th June 2022) - Zhao, Feng; Zhang, Yinyin; Alharthi, Majed; Zafar, Muhammad Wasif
Abstract: Environmental challenges are mounting in the developing world, and mitigation activities, such as improved technology, green energy production, and research and development depend on significant funding from financial institutions. In this context, financial inclusivity can channelize investments towards green energy adoption and technological upgrading. On the flip side, the absence of environmental preferences may lead financial institutions to strengthen pollution‐intensive projects and inefficient production patterns. Thus, this study used the panel quantile regression method to unfold the impacts of financial inclusion (FI) and globalization on CO2 controlling foreign direct investment (FDI), energy prices, and economic growth. The results established that FI boosts pollutant emissions in developing countries, and globalization also mounts environmental deterioration. However, energy prices and FDI contribute to mitigating CO2 in developing nations. Moreover, the Environmental Kuznets Curve is evidenced in the panel of developing nations. As an alternative technique, Driscoll–Kraay regression method validated the consistency of the results. Considering the findings of this study, several policy suggestions are discussed to enhance environmental quality.